THE DIFFERENT C/N RATIO OF QUAIL FECES AND RICE STRAW MIXTURE AFFECTS TEMPERATURE CHANGE, MICROBIAL COUNT, ORGANIC-C CONTENT, AND TOTAL N CONTENT IN EARLY DECOMPOSITION RESULTS - Priyati, Ani; Sujana, Endang; Setiawati, Mieke Rochini; Anas, Anas (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
Livestock waste is one of the factors that must be considered in livestock farming, as it can cause environmental pollution. Quail feces, a type of livestock waste, generally has a low carbon-to-nitrogen ratio, necessitating the supplementation of carbon source from rice straw. Rice straw, which contains high fiber content, is often discarded or burned and has not been utilized by farmers, even though it is suitable for processing into solid or liquid organic fertilizer (POC). Because of the substantial changes in temperature and microbial composition that occur during the composting process, initial breakdown is critical. Using native microbes from quail feces, this study aims to ascertain the impact of the C/N ratio of a mixture of quail feces and rice straw on temperature changes, total microbial count (bacteria, fungi, and actinomycetes), and the content of organic C and total N during the initial decomposition process. This research employed an experimental method with four treatments of C/N ratio mixtures of quail feces and rice straw: 20, 25, 30, and 35. The observed variables included temperature changes, total microbial count (bacteria, fungi, and actinomycetes), and the content of organic C and total N over 14 days of initial decomposition. The best decomposition process was achieved with a C/N ratio of 20, the highest temperature change (thermophilic phase on the second day and a maximum temperature of 65°C), and total counts of bacteria, fungi, and actinomycetes of 9.6 x 1011 cfu/mg, 2.7 x 104 cfu/mg, and 5.6 x 106 cfu/mg, respectively. The organic C content was 37.62%, and the total N content was 3.11% (C/N 12.09).